Nível de atividade física, comorbidades e idade de pacientes hipertensos - Bueno, Denise Rodrigues (2013)
Physical inactivity is associated with chronic diseases in older adults. There are different domains of physical activity, such as leisure and locomotion. This study investigate the associations between different domains of physical activity, comorbidities and aging in hypertensive adults. Participants included 192 hypertensive respondents classified in groups of active and insufficiently active for leisure-time, locomotion, occupation and total time. They were stratified in age groups. Waist circumference was measured and comorbidities were self-reported. The chi-square test analyzed these associations; a one-way ANOVA compared the age groups (significance at p <0.05). The mean total time and occupational physical activity were lower for groups ages over 60 and 70 years, respectively. Occupational activity was associated with age in the female group, and with cholesterol and diabetes in males, who also had physical activity of locomotion associated with waist circumference. Physical activity of hypertensive patients is associated with comorbidities in different age groups and sex.